Design and manufacturing of a hip joint motion simulator with a novel modular design approach - Torabnia, Shams; Mihcin, Senay; Lazoglu, Ismail (International journal on interactive design and manufacturing, 2024)
The study is aimed to develop a hip joint wear simulator using a modular design approach to help experimentally monitor and control critical wear parameters to validate in-silico wear models. The proper control and application of wear parameters such as the range of motion, and the applied force values while estimating the lost material due to wear are essential for thorough analysis of wear phenomena for artificial joints. The simulator's dynamics were first modeled, then dynamic loading data was used to calculate the forces, which were further used for topology optimization to reduce the forces acting on each joint. The reduction of the link weights, connected to the actuators, intends to improve the quality of motion transferred to the femoral head. The modular design approach enables topology-optimized geometry, associated gravitational and dynamic forces, resulting in a cost-effective, energy-efficient product. Moreover, this design allows integration of the subject specific data by allowing different boundary conditions following the requirements of industry 5.0. Overall, the in-vitro motion stimulations of the hip-joint prosthesis and the modular design approach used in the study might help improve the accuracy and the effectiveness of wear simulations, which could lead into the development of better and longer-lasting joint prostheses for all. The subject-specific and society-based daily life data implemented as boundary conditions enable inclusion of the personalized effects. Next, with the results of the simulator, CEN Workshop Agreement (CWA) application is intended to cover the personalized effects for previously excluded populations, providing solution to inclusive design for all.